One world and the many sciences - Melnyk, A; Melnyk, Andrew (1990)
﻿ The subject of this thesis is physicalism, understood not as some particular doctrine pertaining narrowly to the philosophy of mind, but rather as a quite general metaphysical claim to the effect that everything is, or is fundamentally, physical. Thus physicalism explicates the thought that in some sense physics is the basic science. The aim of the thesis is to defend a particular brand of physicalism, which I call eliminative type physicalism. It claims, roughly, that every property is a physical property – a property mentioned in the laws of physics, and hence that any putative property not identifiable with a physical property must be eliminated from our ontology. Eliminative type physicalism is apt to face three objections, and so my thesis, like Caesar's Gaul, falls into three parts. In the first, I argue against the idea that there are tenable positions, both physicalist and non-physicalist, alternative to eliminative type physicalism. I argue that each of these positions – token physicalism (Fodor, middle Putnam), supervenience physicalism (Lewis, Horgan) and and a non-physicalist view I call pluralism (Goodman, late Putnam) – is defective. In the second part, responding to the objection that there is just no reason to be a physicalist, I develop a positive argument for eliminative type physicalism, an argument resting upon a strong version of the explanatory test for reality according to which only explanatorily indispensable properties can justifiably be said to exist. In the third and final part, I argue, against the charge that eliminative type physicalism cannot accommodate what I call phenomenal properties (qualia, raw feels etc.), that there is no good reason to deny, and one good reason to affirm, that phenomenal properties just are physical properties.